2016
DOI: 10.26503/todigra.v2i3.51
|View full text |Cite
|
Sign up to set email alerts
|

Editors of Play: The Scripts and Practices of Co-creativity in Minecraft and LittleBigPlanet

Abstract: Computer games can be described as assemblages which, to use a term borrowed from Science and Technology Studies, provide different scripts, setting the scene for user practices. Scripts include the game world’s possibilities, restrictions, and the degree of freedom provided tothe player. Lately, a new genre of games challenges these specifics. Socalled editor games, like Minecraft or LittleBigPlanet, which entered the market with sweeping success, are not games in the traditional sense (in which players follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…From the perilous survival challenges of Survival Mode to the limitless creative possibilities of Creative Mode, Minecraft's array of gameplay options is a testament to its enduring appeal (Narwal & Aggarwal, 2022;Supraja et al, 2022). In this exploration, we embark on a journey through Minecraft's varied game modes, uncovering their distinct features and applications within the ever-evolving Minecraft universe (Abend & Beil, 2015; C. C. R. G. de Sena & Jordão, 2020) Minecraft offers a wide array of benefits to players, making it a beloved and versatile game for individuals of all ages. For instance, on this research, we found that there are eight benefits, 1) Minecraft is often described as a digital sandbox, providing players with a vast canvas to express their creativity (Landay, 2016).…”
Section: Findings Enhancing and Developing Arabic Learning Through Mi...mentioning
confidence: 99%
“…From the perilous survival challenges of Survival Mode to the limitless creative possibilities of Creative Mode, Minecraft's array of gameplay options is a testament to its enduring appeal (Narwal & Aggarwal, 2022;Supraja et al, 2022). In this exploration, we embark on a journey through Minecraft's varied game modes, uncovering their distinct features and applications within the ever-evolving Minecraft universe (Abend & Beil, 2015; C. C. R. G. de Sena & Jordão, 2020) Minecraft offers a wide array of benefits to players, making it a beloved and versatile game for individuals of all ages. For instance, on this research, we found that there are eight benefits, 1) Minecraft is often described as a digital sandbox, providing players with a vast canvas to express their creativity (Landay, 2016).…”
Section: Findings Enhancing and Developing Arabic Learning Through Mi...mentioning
confidence: 99%
“…The possibilities for re-scripting in computing are readily apparent in studies of creativity which examine scripts in the context of participatory "open world" games (Abend and Beil 2016) and in the development of software for artistic performance (Carey 2016). As Pollock (2005, 504) argues in a study of improvisation in the work of software programming, "to program is to perform work-arounds, to bypass constraints, and to rewrite code."…”
Section: Uncertaintymentioning
confidence: 99%
“…The possibilities for re-scripting in computing are readily apparent in studies of creativity which examine scripts in the context of participatory “open world” games (Abend and Beil 2016) and in the development of software for artistic performance (Carey 2016). As Pollock (2005, 504) argues in a study of improvisation in the work of software programming, “to program is to perform work-arounds, to bypass constraints, and to rewrite code.” Computing systems not only carry scripts to be negotiated between users and designers but also embed prospects for radical change, as their general-purpose material bases make the scripts of computing open-ended to re-scripting.…”
Section: Unstable Scriptsmentioning
confidence: 99%
“…Editor Games, wie Little Big Planet (SCE Cambridge Studio 2008) oder Minecraft (Mojang AB/4 J Studios 2011), dar, die eine Verschmelzung aus ‚klassischem' Spiel und kreativem Baukasten-System erproben (vgl. Abend und Beil 2015).…”
Section: Gaming Culturesunclassified